The Resilience of the Main Character in the Film Farha (2021): A Structuralist Analysis - Wafa Fatimatuzzahra; Irfan Addriadi; Khomisah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aims to analyze the forms of resilience exhibited by the main character in the film Farha (2021) by Darin J. Sallam, as well as to examine how the film’s intrinsic elements work together to construct the meaning of that resilience. This film was selected because it depicts the traumatic experiences of a Palestinian teenage girl living amidst the 1948 Nakba tragedy, while also showcasing the protagonist’s struggle in facing psychological pressure, fear, and alienation during the war. This study was conducted by integrating Wellek and Warren’s structuralism with Michael Ungar’s multisystemic resilience theory. The research method used is qualitative descriptive, with research data consisting of scenes, conflicts, and visual elements that demonstrate the main character’s resilience process. Data was collected through the watch and note technique by watching the film repeatedly, then selecting scenes relevant to the research focus. The results of the analysis show that the character Farha’s resilience is constructed through three main forms adaptive negotiation, ecological resilience, and meaning-making, which evolve alongside changes in the conflict and the character’s psychological state. Additionally, intrinsic elements such as characterization, plot, setting, conflict, and visual symbols such as confined spaces and the sky play a crucial role in reinforcing the portrayal of the protagonist’s resilience. Through this approach, the researcher asserts that resilience in the film Farha is a process of adaptation and transformation rooted in the character’s inner strength and the social and cultural values that underpin it, thereby enriching film studies through an interdisciplinary approach that bridges literary structuralism and contemporary psychosocial perspectives.